Using qualitative and co-design methods to inform the development of an intervention to support and improve physical activity in childhood cancer survivors: a study protocol for BEing Active after ChildhOod caNcer (BEACON). Issue 12 (21st December 2020) - Brown, Morven C; Araújo-Soares, Vera; Skinner, Roderick; Glaser, Adam W; Sarwar, Naseem; Saxton, John M; Montague, Kyle; Hall, Jamie; Burns, Olivia; Sharp, Linda
Abstract : Introduction: Childhood cancer survivors (CCSs) treated with cardiotoxic cancer treatments are at increased risk of developing cardiometabolic complications. This risk is further exacerbated by poor health behaviours. In particular, CCSs are less active than non-cancer comparators. Existing interventions aiming to improve physical activity (PA) levels in CCSs are methodologically weak. The aim of this study is to rigorously and systematically develop an evidence-based and theoretically-informed intervention to promote, support, improve and sustain PA levels in CCSs, with the long-term goal of reducing CCSs' cardiovascular morbidity and mortality. Methods and analysis: The BEing Active after ChildhOod caNcer (BEACON) study involves two workpackages at two National Health Service sites in England, UK. Participants will be CCSs and their parents, and healthcare professionals (HCPs) involved in their care. Workpackage one (WP1) will use qualitative methods to explore and understand the barriers and facilitators to PA in CCSs. Two sets of semistructured interviews will be conducted with (1) CCSs (aged 10–24 years) and (2) parents of CCSs. WP2 will use co-design methods to bring together stakeholders (CCSs; their parents; HCPs; researchers) to develop a prototype intervention. Where possible, all data will be audio recorded and transcribed . Data from WP1 will be analysed using a thematic approach. Analysis of WP2 data will involve content analysis, and analysis of formative output and procedures. Ethics and dissemination: The study was approved by North East-Tyne & Wear South Research Ethics Committee (REC ref: 18/NE/0274). Research findings will be disseminated primarily via national and international conferences and publication in peer-reviewed journals. Patient and public involvement will inform further dissemination activities.